Feasibility Analysis Of JKM White Oyster Mushroom - Roy Saputra; Rika Dwi Yulihartika; Heri Fariadi (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose: This study aims to analyze the business feasibility of the JKM white oyster mushroom enterprise located in Bentiring Village, Muara Bangkahulu District, Bengkulu City. Methodology: This research uses a quantitative descriptive analysis approach with data analysis methods including Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit Cost Ratio (Net B/C), and sensitivity analysis. The respondent was determined using a purposive sampling technique, with the business owner serving as the sole respondent. Results: The findings reveal that the positive NPV value indicates net benefits received throughout the business period, while the IRR, which is significantly above the minimum required return, reinforces the strong profit potential. Although the Net B/C value of 0.92 is slightly below one, this indicator is still acceptable as it is supported by other strong feasibility indicators. In addition, the ROI was found to be 12%. Findings: The JKM white oyster mushroom business in Bentiring Village, Muara Bangkahulu District, Bengkulu City is declared feasible.Novelty: The JKM mushroom business has never been previously studied. Conclusion: This study indicates that the business is capable of providing a competitive rate of return. Overall, the evaluation results show that the business is feasible to be developed as it offers good and sustainable financial prospects. Paper Type: Research Article.